MEDIASI PERBANKAN SEBAGAI UPAYA PENYELESAIAN SENGKETA ANTARA BANK DAN NASABAH ( STUDI PADA PT. BANK SUMUT CABANG UTAMA) - SALSA BHILA (University of North Sumatera, 2013)
Abstrak : Practice transactions between bank customers can not be separated from risk. One of the risks is often the case that the dispute between the bank and the customer. When the legal relationship between banks and customers began to create, since it opens the possibility of disputes between the pihak.penyelesaian dispute between the customer and the bank can be done through arbitration, the courts or through alternative dispute resolution is by way of mediation. The effectiveness of dispute resolution through mediation banking banking is very good for the customers and the bank. The problem posed in this thesis is How the disputes between banks and customers in both the legal relationship under the law of Indonesia's banking system, how the factors that cause sengkta between the bank and the customer, alternative forms of dispute resolution that can be used by banks and customer and stages of conflict resolution between the bank and the customer through the process of mediation. The method used in writing this paper is the normative and empirical, with literature data collection (library research) that collect data and read references through regulation, the Internet, and other sources are then selected appropriate data to support the writing. Of writing this thesis it can be concluded the protection of customers' influence on the banking industry. This is because the banking business is closely related to trust. If people believe in a bank, they will feel safe to be customers of the bank in question otherwise distrust will greatly affect business continuity when a bank.untuk that disputes between banks and customers must be resolved. Dispute resolution through mediation is very beneficial, since the completion of a simple, inexpensive, and cepat.Mediasi is a method of problem solving that is not to win one of the parties to the dispute, but rather find the best solution that both parties to the dispute are satisfied without feeling lost Keywords: Banking Mediation, Dispute, Customer